Impact of Physical Activity on the Association Between Unhealthy Adolescent Behaviors and Anxiety Among Korean Adolescents: A Cross-sectional Study - Hyo-jung Lee; Jeong Pil Choi; Kunhee Oh; Jin-Young Min; Kyoung-Bok Min (Korean Society for Preventive Medicine, 2023)
Objectives Adolescents who engage in unhealthy behaviors are particularly vulnerable to anxiety. We hypothesized that participation in physical activity could influence the relationship between anxiety and unhealthy behaviors in adolescents. These behaviors include smoking, alcohol consumption, and unsafe sexual activity. Methods This study included 50 301 students from the first year of middle school to the third year of high school, all from Korea. The unhealthy adolescent behaviors examined included current alcohol consumption, current smoking, and unsafe sexual behavior. Anxiety levels were assessed using the Generalized Anxiety Disorder-7 questionnaire (GAD-7). Results The participants had a mean age of 15.19 years and an average GAD-7 score of 4.23. No significant differences were observed in GAD-7 score among exercising participants when categorized by smoking status (p=0.835) or unsafe sexual behavior (p=0.489). In contrast, participants in the non-exercise group who engaged in these behaviors demonstrated significantly higher GAD-7 scores (p<0.001 and 0.016, respectively). The only significant interaction was found between unsafe sexual behavior and exercise (p=0.009). Based on logistic regression analysis, within the non-exercise group, significant positive associations were observed between current smoking and anxiety (odds ratio [OR], 1.36; 95% confidence interval [CI], 1.18 to 1.57), as well as between unsafe sexual behavior and anxiety (OR, 1.33; 95% CI, 1.02 to 1.73). However, within the exercise group, no significant association was found between anxiety and either smoking or unsafe sexual behavior. Furthermore, no significant interaction was observed between unhealthy behaviors and exercise. Conclusions These findings are insufficient to conclude that physical activity influences the relationship between unhealthy behaviors and anxiety.